Inflation analysis in Indonesia: A monetary or fiscal phenomenon? - Indarti, Dwi; Saraswati, Birgitta Dian; Sasongko, Gatot (Industrija, 2024)
Abstract: This study seeks to identify and analyze the effects of monetary phenomena (operationalized with the quantity of money supply and interest rates), fiscal phenomena (operationalized with fiscal deficits), and the implementation of inflation-targeting monetary policies on inflation rates in Indonesia. Using Engle-Granger's Error Correction Model (EG-ECM) and time-series data of 1990-2020, this study empirically demonstrates that interest rates negatively affect inflation rates in Indonesia in both the short-run and long-run. Further, the EG-ECM estimation results suggest that inflation in Indonesia is a monetary phenomenon, as indicated by the significantly negative impact of interest rates on inflation rates in both the short and long runs. Inflation in Indonesia is not a fiscal phenomenon because fiscal deficits do not affect inflation rates in both the short and long runs. Besides, we also document that ITF policies negatively affect inflation rates in the long run. Our study implies that an inflation-targeting monetary policy framework remains effective in maintaining price stability in Indonesia. The current ITF policy is flexible and can control publicly expected inflation since its implementation in 2005, leading to stable inflation rates.